2014
DOI: 10.1590/0102-311x00050013
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao obito neonatal de recem-nascidos de alto risco: estudo multicentrico em Unidades Neonatais de Alto Risco no Nordeste brasileiro

Abstract: Este estudo pretendeu determinar os fatores associados à mortalidade intra-hospitalar, utilizando como variáveis explicativas as características individuais da mãe, da assistência ao pré-natal, parto e período neonatal e dos recém-nascidos internados em Unidades Neonatais de Alto Risco (UTIN) integrantes da Rede Norte-Nordeste de Saúde Perinatal no Nordeste do Brasil. Foi realizado estudo longitudinal, multicêntrico de base hospitalar. A população do estudo compreendeu 3.623 nascidos vivos internados em 34 UTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
31

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 25 publications
1
30
0
31
Order By: Relevance
“…Studies show that more important than the number of medical visits is the quality of these visits. The studies also show that professionals must be ready to provide services to pregnant women in a way that they can identify potential problems and risks to the woman and the fetus, promoting the reduction of diseases such as: prematurity; low weight at birth; and long hospitalization in intensive care units that increase public expenses related to potentially preventable morbidity and mortality during pregnancy (5,8) . The improvement of prenatal care quality in Brazil could prevent those maternal and infant deaths considered to be preventable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that more important than the number of medical visits is the quality of these visits. The studies also show that professionals must be ready to provide services to pregnant women in a way that they can identify potential problems and risks to the woman and the fetus, promoting the reduction of diseases such as: prematurity; low weight at birth; and long hospitalization in intensive care units that increase public expenses related to potentially preventable morbidity and mortality during pregnancy (5,8) . The improvement of prenatal care quality in Brazil could prevent those maternal and infant deaths considered to be preventable.…”
Section: Discussionmentioning
confidence: 99%
“…In that period, vulnerability to socio-economic conditions, basic sanitation, health care, and access to preventive and healing services remains (7) . Most deaths were in the first days of life, while infants were still in the neonatal and pediatric intensive care units as a consequence of premature birth, intrapartum asphyxia, and gestational condition (8) . On the other hand, children released from maternity after birth are expected to be monitored by the health service: to control growth and development; and because this age group is more susceptible and vulnerable to diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (12) found that variables associated with death until the 27th day of life were type of delivery, notusing antenatal corticosteroids, preeclampsia, birth weight < 2500g, Apgar score < 7 at 5 minutes, endotracheal intubation, and notusing exogenous surfactant. For these authors, death was determined by the conditions of the pregnancy, delivery and the newborn.…”
Section: Discussionmentioning
confidence: 99%
“…We also call attention to the risk in the current and previous pregnancy (prior stillbirth, premature or low birth weight infants), the movement of the pregnant woman to delivery and women giving birth to low-weight babies (< 1,500 grams) in hospitals not equipped with a Neonatal Intensive Care Unit (NICU) (4) . Studies show that among newborns in NICU, Cesarean birth, failure to use steroids, pre-eclampsia, oligohydramnios, <2,500 grams at birth, Apgar<7 in the fifth minute of life, endotracheal intubation and failure to use a surfactant are also associated with neonatal death (8) . Death in this period reflects socioeconomic and reproductive conditions, and is also related to the quality of pre-natal care and care during delivery, revealing gaps in the healthcare network (9)(10) .…”
Section: Objectivementioning
confidence: 99%